Enterprise Modeling in the context of Enterprise Engineering: State of the art and outlook - François Vernadat (International Journal of Production Management and Engineering)
Enterprise Modeling is a central activity in Enterprise Engineering and can facilitate Production Management activities. This state-of-the-art paper first recalls definitions and fundamental principles of enterprise modelling, which goes far beyond process modeling. The CIMOSA modeling framework, which is based on an event-driven process-based modeling language suitable for enterprise system analysis and model enactment, is used as a reference conceptual framework because of its generality. Next, the focus is on new features of enterprise modeling languages including risk, value, competency modeling and service orientation. Extensions for modeling collaborative aspects of networked organizations are suggested as research outlook. Major approaches used in enterprise modeling are recalled before concluding.